Changes of thyroid antibodies after thermal ablation of thyroid nodules: a retrospective study - Li, Song; Wei, Ying; Zhao, Zhen-long; Peng, Li-li; Li, Yan; Yu, Ming-an (Frontiers in Endocrinology, 2025)
ContextThermal ablation (TA) is increasingly used as a minimally invasive treatment for thyroid nodules; however, its influence on thyroid autoimmunity remains unclear.ObjectiveTo investigate longitudinal changes in thyroid autoantibodies and identify relevant risk factors.MethodsThis retrospective study included 222 patients who underwent TA between April 2020 and September 2023. Serum levels of anti-thyroglobulin antibody (TGAb), anti-thyroid peroxidase antibody (TPOAb), and thyrotropin receptor antibody (TRAb) were measured at baseline and at 1, 6, 12, and 24 months post-ablation. Antibody trajectories, abnormality rates, and associated risk factors were analyzed.ResultsTGAb and TRAb levels increased significantly at all post-ablation time points compared to baseline (all p < 0.05), while TPOAb showed a delayed but significant elevation beginning at 6 months. New-onset antibody positivity was observed in 16.2% of patients, including 9.0% with transient elevations, 4.1% with persistent positivity, and 3.2% with late-onset elevation. Among patients with transient elevations, 93.1% normalized within 24 months. At the 1-month follow-up, patients with benign nodules had more frequent antibody abnormalities than those with papillary thyroid carcinoma (9.5% vs. 2.7%, p = 0.045), although no significant differences were observed at subsequent time points. Multivariate analysis identified papillary thyroid carcinoma (OR = 7.70, p = 0.035), baseline TGAb (OR = 1.08, p < 0.001), and baseline TPOAb (OR = 1.12, p = 0.023) as independent predictors of post-ablation antibody abnormalities. ROC analysis demonstrated that a baseline TGAb level ≥17.32 IU/mL had moderate predictive value (AUC = 0.746), with a specificity of 85.5% and a negative predictive value of 91.9%.ConclusionThermal ablation was associated with transient increases in thyroid autoantibodies. A baseline TGAb level ≥17.32 IU/mL, elevated TPOAb, and a diagnosis of papillary thyroid carcinoma are associated with increased risk.